Analysis and diagnostic of proppant flowback in the Orito field, Colombia - Varela, A.; Saavedra, Nestor (CT&F - Ciencia, Tecnología y Futuro, 2000)
Hydraulic fracturing is a conventional practice for production enhancement in low production and damaged wells. Proppant flowback has been a concern in hydraulic fracturing since proppant began to be used as fracture supporting material. In order to prevent the usual proppant flowback problems, some wells in the Orito field were fractured using curable resin coated proppant (RCP). However, flowback production of proppant from some hydraulically fractured wells has caused some serious operational problems, demanding additional analysis of the problem and field handling procedures. This paper describes the laboratory tests and field considerations to design the tests, taken into account to analyze and diagnose the proppant flowback problem in the Orito field. Two types of tests were performed i.e., displacement and flowback.